1996
DOI: 10.1083/jcb.134.6.1387
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic measurement of the pH of the Golgi complex in living cells using retrograde transport of the verotoxin receptor.

Abstract: Abstract. The B subunit of verotoxin (VT1B) from enterohemorrhagic Escherichia coli is responsible for the attachment of the holotoxin to the cell surface, by binding to the glycolipid, globotriaosyl ceramide. After receptor-mediated endocytosis, the toxin is targeted to the Golgi complex by a process of retrograde transport. We took advantage of this unique property of VT1B to measure the pH of the Golgi complex in intact live cells. Purified recombinant VT1B was labeled with either rhodamine or fluorescein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
120
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 38 publications
16
120
2
Order By: Relevance
“…However, no obvious colocalization between B-Glyc-KDEL and the lysosomal marker Lamp-2 was detected. These data are consistent with a recent report on intracellular transport of verotoxin-1 B-fragment (100% similar to Shiga toxin B-fragment) in which no accumulation of B-fragment in lysosomal structures has been detected (40). Interestingly, we found that BFA, which was shown to have only limited effects on transport to lysosomes (49 -52), not only completely abolished glycosylation of B-Glyc-KDEL, but also strongly inhibited the appearance of the putative degradation product of B-Glyc-KDEL.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, no obvious colocalization between B-Glyc-KDEL and the lysosomal marker Lamp-2 was detected. These data are consistent with a recent report on intracellular transport of verotoxin-1 B-fragment (100% similar to Shiga toxin B-fragment) in which no accumulation of B-fragment in lysosomal structures has been detected (40). Interestingly, we found that BFA, which was shown to have only limited effects on transport to lysosomes (49 -52), not only completely abolished glycosylation of B-Glyc-KDEL, but also strongly inhibited the appearance of the putative degradation product of B-Glyc-KDEL.…”
Section: Discussionsupporting
confidence: 82%
“…4, G and H). The same result was obtained for DTAF-labeled wild type B-fragment (not shown), which is in good agreement with previously published experiments on B-fragment transport to the Golgi apparatus (40). However, a fraction of B-Glyc-KDELGL was present in the ER, as documented by colocalization with signal sequence receptor protein (Fig.…”
Section: Fig 4 Colocalization Of B-glyc-kdel and B-glyc-kdelgl Withsupporting
confidence: 81%
“…However, live cell imaging studies reveal that, for several minutes after entering the cell, endocytic probes in early ("sorting") endosomes remain fairly stationary and do not undergo long-range, microtubule-dependent translocations (Kim et al, 1996). Data were acquired from at least two different coverslips in two independent experiments.…”
Section: Association Of Dynactin and Clip-170 At Microtubule Endsmentioning
confidence: 99%
“…Endosomal pH was measured using an FITC pH ratio imaging technique (Kim et al, 1996). Cells overexpressing dynamitin were identified on the basis of Golgi morphology (Texas Red ceramide staining; Molecular Probes), loaded with FITC-␣ 2 -M (0.4 mg/ml) for 20 min at 37°C, then mounted in the heating stage of the microscope.…”
Section: Measurement Of Endosome Phmentioning
confidence: 99%
See 1 more Smart Citation